Senate Panel Likely to Back Reagan's Plan to Gut Science-Education Programs. - McDonald, Kim (Chronicle of Higher Education, 1982)
The article reports that the United States Senate Labor and Human Resources Committee, under the leadership of Orrin G. Hatch, has introduced legislation supporting President Ronald Reagan's proposal to cut all funding for the National Science Foundation's science-education programs for fiscal 1983, except for the $15-million aid for graduate fellowships. Senator Edward M. Kennedy is expected to amend Hatch's bill to increase the $15 million to $25 million.